THE NEGATIVE EFFECTS OF ENVIRONMENTAL DEGRADATION IN WALL-E MOVIE - SHOFA, ENA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: ecocriticism, environment, environmental degradation.Ecocriticism is a call to texts to connect to the issues of today’s environmental crisis. This environmental crisis or environmental degradation is caused by imbalance between living things and environment, so that if one of living things are destroyed, then other living things are exactly influenced.  Then, as it can be seen that there are many negative  effects of environmental degradation which appear in human life. In this study, the researcher analyzes what the negativeeffects of environmental degradation are, as portrayed in Wall-E movie.This research uses qualitative research because  it  concerns  with the result  related to human and their environment.  So, by using qualitative design, the writer needs to read movie script of Wall-E movie to be analyzed. The study uses ecocriticism to help the writer understand more about the relationship between a product of popular culture and environment.The result of the study shows that there are many piles of trash which are from human activities that  cover the earth. The trash causes many negative effects like land pollution, air pollution, water pollution, and so on, so that the earth does not anymore fit for occupancy. The trash which covers the earth causes many negative effects so that  human have to move  to a spacecraft,  Axiom.  Human do the activities  which are  handled by computer.  To develop the earth, the Axiom launches project to search for the plant which remains on the earth.For the next researchers, the writer expects the use of environment theme as the object of the study. Furthermore, the next researchers can provide new perspectives in analyzing the issue. The writer also suggests the use of ecocriticism as an approach which can be applied in the other genres of literary works  and products  of  popular  culture  to enrich the study of  human and environment,  for example a movie entitled Furry Vengeance which tells about how a clever racoon against human to save its habitat, nature, that has been destructed by human.